2016
DOI: 10.1111/bcp.13067
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous adverse drug reaction reports for neonates and infants in the UK 2001–2010: content and utility analysis

Abstract: AIMSThe UK Medicines and Healthcare products Regulatory Agency (MHRA) runs a national spontaneous reporting system (Yellow Card [YC] Scheme) to collect 'suspected' adverse drug reaction (ADR) data. We aim to describe the content and utility of YC reports received for patients aged <2 years. METHODSData on all ADRs reported using YC in infants aged <2 years from the years 2001-10 were supplied by the MHRA. RESULTSFor infants age <2 years, 3496 suspected ADRs were reported using YC (paternal medication pre-conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…Pharmacovigilance among infants exposed to drugs through breastfeeding is not well established, with under--reporting of adverse drug reactions, and a likely skew towards the most serious events 105 . Whilst few studies have systematically collected infant safety data, the recent PROMISE trial showed no increase in toxicities among infants exposed to ART through breast milk, compared to extended infant nevirapine prophylaxis 69 As women living with HIV in high--income settings question their eligibility to breastfeed, and women in LMIC are currently advised to breastfeed without effective counselling on risks, the ethics of policies that argue for or against breastfeeding and the rights of women to choose an infant feeding practice need examination.…”
Section: Exposure To Antiretroviral Drugs Through Breastfeedingmentioning
confidence: 99%
“…Pharmacovigilance among infants exposed to drugs through breastfeeding is not well established, with under--reporting of adverse drug reactions, and a likely skew towards the most serious events 105 . Whilst few studies have systematically collected infant safety data, the recent PROMISE trial showed no increase in toxicities among infants exposed to ART through breast milk, compared to extended infant nevirapine prophylaxis 69 As women living with HIV in high--income settings question their eligibility to breastfeed, and women in LMIC are currently advised to breastfeed without effective counselling on risks, the ethics of policies that argue for or against breastfeeding and the rights of women to choose an infant feeding practice need examination.…”
Section: Exposure To Antiretroviral Drugs Through Breastfeedingmentioning
confidence: 99%
“…There is evidence that the under-reporting noted for ADRs in national spontaneous reporting schemes is as true for children and neonates [35,36] as for adults. As we have seen, knowledge of the potential for nephrotoxicity with aminoglycosides, and an understanding of their pharmacokinetics, has resulted in steps to optimize the dosage.…”
mentioning
confidence: 99%
“…1 The rate of under-report-ing of ADRs has been estimated to be approximately 94% and neonatal ADR reports are not influencing the clinical warnings issued by the MHRA. 2,3 This study aims to compare reports of neonatal ADRs actively collected by a researcher from a tertiary neonatal unit to those reported to the UK yellow card system between 2001 and 2010. Methods An independent researcher collected data on ADRs in a tertiary neonatal care unit by daily ward round attendance, note reviewing and staff questioning.…”
mentioning
confidence: 99%
“…The results collected over four weeks were then compared to the yellow cards submitted to the MHRA between 2001 and 2010 by means of reviewing a recently published paper. 3 Results Between 2001 and 2010 there were ninety seven yellow card reports of neonatal ADRs to the MHRA. Over a four week observational period thirty three neonatal ADR cases were suspected and reported by a researcher.…”
mentioning
confidence: 99%
See 1 more Smart Citation